2022
DOI: 10.3390/md20100649
|View full text |Cite
|
Sign up to set email alerts
|

Structural Investigation of Aaptourinamine by a Novel Module-Assembly-Based Calculation

Abstract: Natural products have various and complicated structures, which is still a challenge for elucidating these compounds, especially for those lacking two-dimensional nuclear magnetic resonance (2D NMR) correlations mainly caused by high C/H ratios or proton-deficient and multiple heteroatoms through the conventional structural analytical methods. We reported a novel module-assembly calculation method named Dooerafa, which included constructing the meta-structures by a grafting method based on the crucial and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…Li et al 96 reported on a marine drug, aaptourinamine, characterized by a novel module-assembly-based calculations. Molecular networkingbased screening led to the discovery of a cyclic heptadepsipeptide from an Endolichenic Xylaria sp.…”
Section: Nuclear Shielding Calculation In Natural Productsmentioning
confidence: 99%
“…Li et al 96 reported on a marine drug, aaptourinamine, characterized by a novel module-assembly-based calculations. Molecular networkingbased screening led to the discovery of a cyclic heptadepsipeptide from an Endolichenic Xylaria sp.…”
Section: Nuclear Shielding Calculation In Natural Productsmentioning
confidence: 99%